Washington meets Wall Street: A closer examination of the presidential cycle puzzle - Roman Kräussl; André Lucas; David R. Rijsbergen; Pieter Jelle van der Sluis; Evert B. Vrugt (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We show that average excess returns during the last two years of the presidential cycle are significantly higher than during the first two years: 9.8 percent over the period 1948 2008. This pattern in returns cannot be explained by business-cycle variables capturing time-varying risk premia, differences in risk levels, or by consumer and investor sentiment. In this paper, we formally test the presidential election cycle (PEC) hypothesis as the alternative explanation found in the literature for explaining the presidential cycle anomaly. PEC states that incumbent parties and presidents have an incentive to manipulate the economy (via budget expansions and taxes) to remain in power. We formulate eight empirically testable propositions relating to the fiscal, monetary, tax, unexpected inflation and political implications of the PEC hypothesis. We do not find statistically significant evidence confirming the PEC hypothesis as a plausible explanation for the presidential cycle effect. The existence of the presidential cycle effect in U.S. financial markets thus remains a puzzle that cannot be easily explained by politicians employing their economic influence to remain in power.
urn:nbn:de:hebis:30-75795
Keywords: E32; G14; P16; 330; Political Economy; Market Efficiency; Anomalies; Calendar Effects; Präsidentschaftswahl; Spillover-Effekt; Finanzmarkt; Markteffizienz; Zeit; USA